Catching Nucleosome by Its Decorated Tails Determines Its Functional States - Sehrawat, Parveen; Shobhawat, Rahul; Kumar, Ashutosh (Frontiers in Genetics, 2022)
The fundamental packaging unit of chromatin, i.e., nucleosome, consists of ~147 bp of DNA wrapped around a histone octamer composed of the core histones H2A, H2B, H3, and H4, in two copies each. DNA packaged in nucleosomes must be accessible to various machinery, including Replication, Transcription, and DNA Damage Repair, implicating the dynamic nature of chromatin even in its compact state. As the tails protrude out of the nucleosome, they are easily accessible to various chromatin-modifying machinery and undergo Post Translation Modifications (PTMs), thus playing a massive role in epigenetic regulation. PTMs can regulate chromatin states via charge modulation on histones, affecting interaction with various Chromatin Associated Proteins (CAPs) and DNA. With the technological advancement, list of PTMs is ever-growing along with their writers, readers, and erasers further, expanding the complexity of an already intricate epigenetic field. In this review, we discuss how specific PTMs on flexible histone tails affect the nucleosome structure and regulate the accessibility of chromatin from a mechanistic standpoint and structural insights into some newly identified PTM-readers interaction.